A NuSTAR and Swift view of the hard state of MAXI J1813−095. Issue 2 (20th May 2022) - Jiang, Jiachen; Buisson, Douglas J K; Dauser, Thomas; Fabian, Andrew C; Fürst, Felix; Gallo, Luigi C; Harrison, Fiona A; Parker, Michael L; Steiner, James F; Tomsick, John A; Ubach, Santiago; Walton, Dominic J
ABSTRACT: We present an analysis of the NuSTAR and Swift spectra of the black hole candidate MAXI J1813−095 in a failed-transition outburst in 2018. The NuSTAR observations show evidence of reflected emission from the inner region of the accretion disc. By modelling the reflection component in the spectra, we find a disc inner radius of R in < 7  r g . This result suggests that either a slightly truncated disc or a non-truncated disc forms at a few per cent of the Eddington limit in MAXI J1813−095. Our best-fitting reflection models indicate that the geometry of the innermost accretion remains consistent during the period of NuSTAR observations. The spectral variability of MAXI J1813−095 from multi-epoch observations is dominated by the variable photon index of the Comptonization emission.